ANALISIS KINERJA KEUANGAN PADA KOPERASI PONDOK PESANTREN (KOPONTREN) WALISONGO DI KOTA SRAGEN - Gita Puspitasari; Rispantyo Rispantyo; Hudi Kurniawanto (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
The purpose of this study is to analyze the financial performance of Kopontren Walisongo in Sragen City from 2018 to 2021 based on the analysis of capital aspects, productive asset quality aspects, liquidity aspects, independence and growth aspects; and to determine the overall condition of Kopontren Walisongo in Sragen City from 2018 to 2021. The technique used in analyzing the data is descriptive analysis guided by the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number:06/Per/Dep.6/ IV/2016. The variables studied are financial performance, namely capital aspects, productive asset quality aspects, liquidity aspects, independence and growth aspects. The data source used in this study comes from secondary data, namely the Annual General Meeting of Walisongo Islamic Boarding School (RAT) from 2018 to 2021. The results obtained from this study from the capital aspect obtained a score of 70,0 (fairly healthy), the quality aspect of productive assets obtained a score of 89,5 (healthy), the liquidity aspect obtained a score of 70,8 (fairly healthy), the independence and growth aspect obtained a score of 77,5 (fairly healthy). Overall, Walisongo Islamic Boarding School is categorized as Fairly Healthy because the average score obtained is 78.8. The Operating Surplus (SHU) from 2018 to 2021 is Rp.122.190.700; Rp.182.062.459; Rp.185.774.017; Rp.175.287.915. The conclusion obtained from this study is that the financial performance of the Walisongo Islamic Boarding School Cooperative (Kopontren) in Sragen City is quite healthy even though it experienced a decline in Operating Surplus (SHU).